IRES-Dependent Translational Control during Virus-Induced Endoplasmic Reticulum Stress and Apoptosis - Hanson, Paul; Zhang, Huifang M.; Hemida, Maged G.; Ye, Xin; Qiu, Ye; Yang, Decheng (Frontiers in Microbiology, 2012)
Many virus infections and stresses can induce endoplasmic reticulum (ER) stress response, a host self defense mechanism against viral invasion and stress. During this event, viral and cellular gene expression is actively regulated and often encounters a switching of the translation initiation from cap-dependent to IRES (internal ribosome entry sites)-dependent. This switching is largely dependent on the mRNA structure of the 5’untranslated region (5’UTR) and on the particular stress stimuli. Picornviruses and some other viruses contain an IRES within their 5’UTR of viral genome and employ an IRES-driven mechanism for translation initiation. Recently, a growing number of cellular genes involved in growth control, cell cycle progression and apoptosis were also found to contain one or more IRES within their long highly structured 5’UTRs. These genes initiate translation usually by a cap-dependent mechanism under normal physiological conditions; however, in certain environments, such as infection, starvation and heat shock they shift translation initiation to an IRES-dependent modality. Although the molecular mechanism is not entirely understood, a number of studies have revealed that several cellular biochemical processes are responsible for the switching of translation initiation to IRES-dependent. These include the cleavage of translation initiation factors by viral and/or host proteases, phosphorylation (inactivation) of host factors for translation initiation, over-production of homologous proteins of cap-binding protein eIF4E, suppression of cap-binding protein eIF4E expression by specific microRNA, activation of enzymes for mRNA decapping, as well as others. Here, we summarize the recent advances in our understanding of the molecular mechanisms for the switching of translation initiation, particularly for the proteins involved in cell survival and apoptosis in the ER stress pathways during viral infections.